Determination of the CKM angle ϕ 3 from a combination of Belle and Belle II results - The Belle and Belle II collaborations; I. Adachi; L. Aggarwal; H. Aihara; N. Akopov; A. Aloisio; S. Al Said; N. Anh Ky; D. M. Asner; H. Atmacan; V. Aushev; M. Aversano; et al. (Journal of High Energy Physics)
Abstract We report a determination of the CKM angle ϕ 3, also known as γ, from a combination of measurements using samples of up to 711 fb −1 from the Belle experiment and up to 362 fb −1 from the Belle II experiment. We combine results from analyses of B + → DK +, B + → Dπ +, and B + → D * K + decays, where D is an admixture of D 0 and D ¯ 0 $$ {\overline{D}}^0 $$ mesons, in a likelihood fit to obtain ϕ 3 = (75.2 ± 7.6) ° . We also briefly discuss the interpretation of this result.